Ethical behavior of students Mahamakut Buddhist University Isan Campus - Sricharumedhiyan, Chakkree; Phrakhrusutheejariyawat,; Suksen, Akchatree; Boonnadee, Phramaha Chaichana; Ketkatuk, Supawat (Interdisciplinary Academic and Research Journal, 2023)
At present, Thai higher education still focuses on the development of morality. Student ethics are very important to the development of Mahamakut Buddhist University because students play an important role in teaching and management as well as administration. Thus, the objectives of this research were 1) to study the ethical behavior of students. Mahamakut Buddhist University Isan Campus 2) to examine and compare the ethical behavior of students at Mahamakut Buddhist University Isan Campus Classified by Individual Factors. The population used in this study was Mahamakut Buddhist University Isan Campus. Northeastern campus studying for an undergraduate degree in the academic year 2022, 960 people, using simple random sampling, is a random sample from the population, which assumes that each unit or each member in the population has an equal chance of being selected, which the sample consisted of 282 people. The statistical data used in the data analysis were frequency, percentage, mean, and standard deviation. The results show that; (1) The majority of responders were 169 females (59.9 percent) and 113 men (40.1 percent). The majority of them (63.5 percent) studied at the Faculty of Education, and the majority of them (168 individuals) obtained a GPA better than 3.00. accounted for 59.6%. (2) Mahamakut Buddhist University Isan Campus students' ethical behavior Overall, the average was very high. When each side was examined separately, it was noticed that compassion had the highest mean, followed by honesty, and discipline had the lowest. When each argument was considered, it was discovered that you are liable for public property. had the best overall average in terms of honesty, it was determined that he was truthful, understood how to respect people, and did not violate their rights. had the best overall average Regarding discipline, it came to light that he followed the competition's regulations. had the best overall average in terms of compassion, he discovered that he was able to assist others. had the most favorable overall average It has been identified that sacrifice. And (3) The results are a comparison of personal parameters of Mahamakut Buddhist University Isan Campus students in the Northeastern Campus with ethical conduct. and various faculties have distinguished ethical standards. There was statistical significance at the. 05 level. There was no variation in ethical behavior comparing students with ranging grade point averages. This contradicts the specified research hypothesis.